Skeletal muscle alterations in patients with acute Covid‐19 and post‐acute sequelae of Covid‐19. Issue 1 (7th January 2022) - Soares, Madu N.; Eggelbusch, Moritz; Naddaf, Elie; Gerrits, Karin H. L.; van der Schaaf, Marike; van den Borst, Bram; Wiersinga, W. Joost; van Vugt, Michele; Weijs, Peter J.M.; Murray, Andrew J.; Wüst, Rob C.I.
Abstract: Skeletal muscle‐related symptoms are common in both acute coronavirus disease (Covid)‐19 and post‐acute sequelae of Covid‐19 (PASC). In this narrative review, we discuss cellular and molecular pathways that are affected and consider these in regard to skeletal muscle involvement in other conditions, such as acute respiratory distress syndrome, critical illness myopathy, and post‐viral fatigue syndrome. Patients with severe Covid‐19 and PASC suffer from skeletal muscle weakness and exercise intolerance. Histological sections present muscle fibre atrophy, metabolic alterations, and immune cell infiltration. Contributing factors to weakness and fatigue in patients with severe Covid‐19 include systemic inflammation, disuse, hypoxaemia, and malnutrition. These factors also contribute to post‐intensive care unit (ICU) syndrome and ICU‐acquired weakness and likely explain a substantial part of Covid‐19‐acquired weakness. The skeletal muscle weakness and exercise intolerance associated with PASC are more obscure. Direct severe acute respiratory syndrome coronavirus (SARS‐CoV)‐2 viral infiltration into skeletal muscle or an aberrant immune system likely contribute. Similarities between skeletal muscle alterations in PASC and chronic fatigue syndrome deserve further study. Both SARS‐CoV‐2‐specific factors and generic consequences of acute disease likely underlie the observed skeletal muscle alterations in both acute Covid‐19 and PASC.